Becoming Other-wise: Transforming International Service-Learning Through Nurturing Cosmopolitanism. (January 2015) - Bamber, Philip M.
This article explores the potential of pedagogical approaches such as International Service-Learning (ISL) to cultivate a cosmopolitan orientation. Founded upon the premise that conceptualisations of transformative learning must be expanded upon to account for the interaction and balance between epistemological and ontological aspects of learning, it seeks to illuminate the barriers that inhibit the transformative nature of such experiences. A group of conditions, processes, and resultant dispositions for cosmopolitan learning are identified as being particularly useful for interpreting the ongoing experience of ISL for 27 students across a range of locations. This framework is exemplified here to develop an understanding of cosmopolitan learning as a transformative process of becoming other-wise: A form of engagement that is fundamentally holistic and relational with a distinct moral dimension. Although ISL has the potential to nurture cosmopolitanism, evidence is presented of a number of factors that tend to militate against this.